Citizen-science based study of the oral microbiome in Cystic fibrosis and matched controls reveals major differences in diversity and abundance of bacterial and fungal species. Issue 1 (1st January 2021) - Willis, Jesse R.; Saus, Ester; Iraola-Guzmán, Susana; Cabello-Yeves, Elena; Ksiezopolska, Ewa; Cozzuto, Luca; Bejarano, Luis A.; Andreu-Somavilla, Nuria; Alloza-Trabado, Miriam; Blanco, Andrea; Puig-Sola, Anna; Broglio, Elisabetta; et al.
ABSTRACT: Introduction : Cystic fibrosis (CF) is an autosomal genetic disease, associated with the production of excessively thick mucosa and with life-threatening chronic lung infections. The microbiota of the oral cavity can act as a reservoir or as a barrier for infectious microorganisms that can colonize the lungs. However, the specific composition of the oral microbiome in CF is poorly understood.Methods : In collaboration with CF associations in Spain, we collected oral rinse samples from 31 CF persons (age range 7-47) and matched controls, and then performed 16S rRNA metabarcoding and high-throughput sequencing, combined with culture and proteomics-based identification of fungi to survey the bacterial and fungal oral microbiome.Results : We found that CF is associated with less diverse oral microbiomes, which were characterized by higher prevalence of Candida albicans and differential abundances of a number of bacterial taxa that have implications in both the connection to lung infections in CF, as well as potential oral health concerns, particularly periodontitis and dental caries.Conclusion : Overall, our study provides a first global snapshot of the oral microbiome in CF. Future studies are required to establish the relationships between the composition of the oral and lung microbiomes in CF.